2023
DOI: 10.1039/d3gc02702c
|View full text |Cite
|
Sign up to set email alerts
|

Red, yellow, green, and blue light-emitting highly crystallized graphene quantum dots derived from lignin: controllable syntheses and light-emitting diode applications

Tian Gao,
Shengnan Guo,
Jiaojiao Zhang
et al.

Abstract: “Lighting up” lignin: synthesis of multicolour-emitting GQDs with high crystallinity from lignin within 12 h and their successful application to multicolour LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…18 It can be found that the C–H signals of L-CQDs are weaker compared to the C–H signals in the corresponding lignin samples, which is due to the demethylation of lignin during the hydrothermal process. 17 The intensity of the absorption peaks of L-CQDs-1–5 at 1595 cm −1 shows a trend of increasing and then decreasing, which is consistent with the fluorescence data (Fig. 3), suggesting that the CC group has a direct effect on the fluorescence performance of L-CQDs.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…18 It can be found that the C–H signals of L-CQDs are weaker compared to the C–H signals in the corresponding lignin samples, which is due to the demethylation of lignin during the hydrothermal process. 17 The intensity of the absorption peaks of L-CQDs-1–5 at 1595 cm −1 shows a trend of increasing and then decreasing, which is consistent with the fluorescence data (Fig. 3), suggesting that the CC group has a direct effect on the fluorescence performance of L-CQDs.…”
Section: Resultssupporting
confidence: 86%
“…The hydrothermal method provides high-temperature and high-pressure reaction conditions, similar to the chemical reaction environment of the crusting reaction, which promotes the formation and growth of aromatic compounds. 17 Based on the similar absorption characteristics of the UV spectra of L-CQDs and the similar optimal excitation wavelengths and emission wavelengths, it can be reasonably assumed that the L-CQDs formed from lignin with different molecular weights using the hydrothermal method have similar core–shell structures. 34 The difference in the fluorescence intensity of L-CQDs is due to the different content of conjugated structures in their carbon cores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, the aromatic refusing of heterogeneous lignin oligomers occurred by means of the prompt π–π stacking and increased sp 2 hybridization. 23 The cleaved lignin ethers disassembled the methyl groups to generate aromatic molecules with phenolic hydroxyls. Subsequently, the lignin aliphatic alcohol structure can be attacked via hydroxide ions, thus removing hydrogen atoms to form carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%